One leptoquark to rule them all: a minimal explanation for RD(∗), RK and (g−2)[mu] - Bauer, Martin; Neubert, Matthias (Arxiv, 2016)
We show that by adding a single new scalar particle to the Standard Model, a TeV-scale leptoquark with the quantum numbers of a right-handed down quark, one can explain in a natural way three of the most striking anomalies of particle physics: the violation of lepton universality in $\bar B→\bar K\ell^+\ell^-$ decays, the enhanced $\bar B→ D^{(*)}τ\barν$ decay rates, and the anomalous magnetic moment of the muon. Constraints from other precision measurements in the flavor sector can be satisfied without fine-tuning. Our model predicts enhanced $\bar B→\bar K^{(*)}ν\barν$ decay rates and a new-physics contribution to $B_s\!-\!\bar B_s$ mixing close to the current central fit value.